The Influence of Cultural Interference on EFL Students’ Writing Skill The Case of Third Year LMD EFL Students at Laghouat University - DJELITA , Ali; DJENNAD, Djamal; CHERFAOUI, Samia (Faculty of Letters and Foreign Languages Department of English, 2017)
The present thesis is an attempt to investigate the influence of cultural interference on the learners‟ writing skills of English as foreign language (EFL). According to many researches, like many Arab student , the Algerian students commit many mistakes in their English writing, because their writings are based on their own cultural background. Therefore, if the Algerian students have a cultural awareness on their own culture and the target culture they would write correctly in English. The reason behind this weaknesses, and find some solutions in order to overcome these problems. To accomplish this study, a questionnaire has been given to third year EFL students in the department of English at Laghouat University. The results of this study, have confirmed our hypothesis that students‟ own culture affects their writing production negatively, and they have to be aware of the culture, in order to overcome any writing problems. We have represented some useful recommendations in this research that would help students to enhance their writing level in general and raise cultural awareness about the target culture